45th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2009
DOI: 10.2514/6.2009-5088
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis of the Electrospray Plume from an Externally Wetted Tungsten Ribbon Emitter

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden to Department of Defense, Washington Headquarters Services Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Previous work on externally wetted emitters has shown that the emission mode of a single emitter can be shifted by changing ('"" which in turn affects the rate of liquid transport to the tip. 7 The difference in V, xl for the two emitters here likely indicates a similar shift in propellant flow rate and subsequently in the emission mode of the thruster.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Previous work on externally wetted emitters has shown that the emission mode of a single emitter can be shifted by changing ('"" which in turn affects the rate of liquid transport to the tip. 7 The difference in V, xl for the two emitters here likely indicates a similar shift in propellant flow rate and subsequently in the emission mode of the thruster.…”
Section: Discussionmentioning
confidence: 73%
“…Angles of approximately ± 40 degrees are achieved, which allows for the measurement of the ion emission properties of the Taylor cone-jet as a function of emitter angle. The entire ion extraction source is held in vacuum of-1 x I0" 7 Torr. Extraction voltages (f'",) of ± 1200 -1500 V are used, operated in alternating polarity (AC) mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated baseline reading between ±15°, which has been observed previously in needle mass spectra, is attributed to large m/q species that are not completely filtered out by the mass filter and reach the detector. 22,23 It is possible to use the intensity trend of each species to approximate the location of origin of that species in the Taylor cone. Maximum n = 0 cation intensities are observed at high angle values.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Alteration of the needle emitter surface has been shown to impact the intensity ratio of ion species as well as the quantity and mass-to-charge of droplets emitted, again determined through the use of near-field measurements. [8,9] This alteration is likely the result of flow rate modification of the ionic liquid propellant, although no direct measurement of the flow rate was possible. We have previously reported on the effects of volumetric flow rate on the emitted ion species from a capillary-style emitter employing the ionic liquid BMI-DCA (1-butyl-3methylimidazolium dicyanamide).…”
Section: Introductionmentioning
confidence: 99%